2006
DOI: 10.1530/eje.1.02286
|View full text |Cite
|
Sign up to set email alerts
|

R990G polymorphism of the calcium-sensing receptor and renal calcium excretion in patients with primary hyperparathyroidism

Abstract: Context: Primary hyperparathyroidism (PHPT) shows a great variability in clinical course and severity. Data concerning the association between polymorphic variants of the gene encoding the calciumsensing receptor (CaSR) and clinical characteristics of PHPT are not conclusive. Objective: To evaluate the frequency of three polymorphisms; A986S, R990G, and Q1011E of CaSR in patients with PHPT and to correlate the genotypes with clinical and biochemical parameters. Patients and methods: The study included 94 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 34 publications
3
63
2
4
Order By: Relevance
“…This would render the parathyroid cells more prone to proliferation and eventually increase the risk of developing PHPT (20). However, two subsequent studies carried out in German and Italian PHPT patients did not detect any positive correlations between the A986S or R990G variants and the risk of PHPT (9,21). The different conclusions drawn from the present study and the previous studies suggest that racial differences may influence the observed associations between genotypes and PHPT.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…This would render the parathyroid cells more prone to proliferation and eventually increase the risk of developing PHPT (20). However, two subsequent studies carried out in German and Italian PHPT patients did not detect any positive correlations between the A986S or R990G variants and the risk of PHPT (9,21). The different conclusions drawn from the present study and the previous studies suggest that racial differences may influence the observed associations between genotypes and PHPT.…”
Section: Discussioncontrasting
confidence: 93%
“…Additional ethnic-specific studies are necessary to reach a definite conclusion. In Italian populations, the R990G allele has been found to be associated with hypercalciuria in idiopathic calcium stone formers, osteoporotic women, and patients with PHPT (9,10,27). In addition, the R990G SNP has been found to be associated with idiopathic nephrolithiasis in individuals of different ancestries including Canadian, Iranian, and European stone formers and the general population (28,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, common variants of the CASR gene modulate the effect of PTH-related hypercalcaemia on renal calcium handling ( Table 4). The 990G allele, located in the cytoplasmic tail of the receptor protein, has been associated with increased renal calcium excretion in PHPT Italian patients (78,79). Two further single nucleotide polymorphisms (SNPs), located in the regulatory region of the CASR gene, rs7652589 and rs1501899, are associated with kidney stones occurrence in PHPT patients (80).…”
Section: Calcium-sensing Receptor (Casr)mentioning
confidence: 99%
“…This SNP has been associated with primary hypercalciuria, 8 lower circulating calcium in healthy individuals 9 and with lower plasma PTH in patients with primary or sHPT. 10,11 Patients with the glycine allele show a more pronounced suppression of PTH after administration of cinacalcet, as compared with homozygous arginine carriers. 12 Transfected cells expressing CASR with glycine in position 990 respond more strongly to a calcimimetic added to the culture medium than those with arginine.…”
Section: Introductionmentioning
confidence: 99%